EFFECT OF ENTREPRENEURSHIP EDUCATION ON JOB CREATION AMONG UNDERGRADUATES OF BENUE STATE UNIVERSITY MAKURDI, BENUE STATE - KSM1Frank Terna Usa-adi FCNA; Umogbai, Dr. (Mrs.) M. E. (IJRDO - Journal of Business Management, 2022)
This study examines the effect of entrepreneurship education on job creation among undergraduates of Benue State University Makurdi, Benue State. survey research design was adopted to collect primary data from the study area. The population of this study consist 2,974 students of 300 level who are offering entrepreneurship in the study area. Taro Yamane’s formula (1964) was used to calculate the sample size at 353 respondents from the study area. The confirmatory factor analysis was used to test for the construct validity while the Cronbach Alpha coefficient statistics was used to assess the reliability of the instrument. The result shows that the instrument is valid and reliable. Descriptive statistics was used to analyze the demographic characteristics of the respondents and the opinions of the respondents on the specific objectives of the study while multiple regression analysis was used to determine the effect of the independent variables of the study on the dependent variable. The hypotheses of the study were tested using the probability values of the regression estimates. The result of the study indicates that psychomotor education (PYCE) has a positive effect on job creation (JOBC) among undergraduate students of Benue State University in Makurdi Metropolis, Benue State and the effect is not statistically significant (p>0.05) and not in line with a priori expectation. Affective education as the independent variables of the study has a positive effect on job creation among undergraduate students of Benue State University in Makurdi Metropolis, Benue State and the effect is statistically significant and in line with earlier stated a priori expectation which stated a positive effect of the variable on the dependent variable of the study. Cognitive education (COGE) has a positive effect on job creation among undergraduate students of Benue State University in Makurdi Metropolis, Benue State and the effect is statistically significant (p<0.05) and in line with a priori expectation. It was concluded that affective education and cognitive education are positive and significant predicator of job creation in the study area. It was recommended among others that cognitive education should be taught by a much more experienced lecturer as it requires the bringing out and stimulating the latent talents of the student to achieve the best they can through multitasking activities that will challenge the students to think outside the box.